Estimating Poverty among Refugee Populations: A Cross-Survey Imputation Exercise for Chad - Theresa Beltramo; Hai-Anh Dang; Ibrahima Sarr; Paolo Verme (Institute of Labor Economics (IZA), 2021)
Household consumption surveys do not typically cover refugee populations, and poverty estimates for refugees are rare. This paper tests the performance of a recently developed cross-survey imputation method to estimate poverty for a sample of refugees in Chad, combining survey and administrative data collected by the United Nations High Commissioner for Refugees. The proposed method offers poverty estimates based on administrative data that are mostly statistically insignificantly different from those based on survey consumption data. This result is robust to different poverty lines, sets of regressors, and modeling assumptions of the error terms. We find the method to outperform common targeting methods, such as proxy means tests and the targeting method that is currently used by humanitarian organizations in Chad.
Keywords: C15; F22; I32; O15; O20; 330; refugees; forced displacement; poverty; imputation; targeting; Chad